European Surveillance System on Contact Allergies (ESSCA): results with the European baseline series, 2013/14. (13th August 2017) - Uter, W.; Amario‐Hita, J.C.; Balato, A.; Ballmer‐Weber, B.; Bauer, A.; Belloni Fortina, A.; Bircher, A.; Chowdhury, M.M.U.; Cooper, S.M.; Czarnecka‐Operacz, M.; Dugonik, A.; Gallo, R.; et al.
Abstract: Background: Contact allergy is a common condition and can severely interfere with daily life or professional activities. Due to changes in exposures, such as introduction of new substances, new products or formulations and regulatory intervention, the spectrum of contact sensitization changes. Objective: To evaluate the current spectrum of contact allergy to allergens present in the European baseline series (EBS) across Europe. Methods: Retrospective analysis of data collected by the European Surveillance System on Contact Allergies (ESSCA, www.essca-dc.org ) in consecutively patch‐tested patients, 2013/14, in 46 departments in 12 European countries. Results: Altogether, 31 689 patients were included in the analysis. Compared to a similar analysis in 2004, the prevalence of contact allergy to methylisothiazolinone went up to around 20% in several departments. In comparison, contact allergy to the metals nickel, cobalt and chromium remained largely stable, at 18.1%, 5.9% and 3.2%, respectively, similar to mostly unchanged prevalence with fragrance mix I, II and Myroxylon pereirae (balsam of Peru) at 7.3%, 3.8% and 5.3%, respectively. In the subgroup of departments diagnosing (mainly) patients with occupational contact dermatitis, the prevalence of work‐related contact allergies such as epoxy resin or rubber additives was found to be increased, compared to general dermatology departments. Conclusion: Continuous surveillance of contact allergy based on network data offers the identification of time trends or persisting problems, and thus enables focussing in‐depth research (subgroup analyses, exposure analysis) on areas where it is needed.